2021
DOI: 10.1186/s12884-021-04225-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine profile in women with moderate to severe anxiety and depression during pregnancy

Abstract: Background Cytokine levels have been extensively described in pregnant subjects under normal and pathological conditions, including mood-related disorders. Concerning chemokines, very few studies have reported their association with psychiatric disorders during pregnancy. Therefore, we explored the chemokine profile in women exhibiting anxiety and depression during late pregnancy in the present study. Methods One hundred twenty-six pregnant women i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 82 publications
1
14
0
Order By: Relevance
“…It has been reported that the serum levels of MIP-1β were significantly increased in pregnant women with anxiety and depression compared to the control group, and a positive relationship was found between MIP-1β levels and severity of depressive symptoms. 17 However, another study have shown that the serum levels of MIP-1β was significantly decreased in patients with MDD compared to healthy controls. 18 The source of the contradictions between these reports remains unclear.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that the serum levels of MIP-1β were significantly increased in pregnant women with anxiety and depression compared to the control group, and a positive relationship was found between MIP-1β levels and severity of depressive symptoms. 17 However, another study have shown that the serum levels of MIP-1β was significantly decreased in patients with MDD compared to healthy controls. 18 The source of the contradictions between these reports remains unclear.…”
Section: Discussionmentioning
confidence: 97%
“…There also are reports on an association between IP-10 and depressive symptoms as well as sickness behaviour, cognitive impairment, fatigue and mood changes [23,24]. In a recent study on pregnant patients with high levels of anxiety and depressive symptoms, IP-10 was signi cantly increased [25]. In older patients with neuropsychiatric disorders, serum IP-10 was associated with sleep disturbances [26].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that elevated serum cytokines and chemokines during pregnancy were positively correlated with depressive and anxiety symptoms [17,59], suggesting that cytokines and chemokines may be involved in depression and anxiety during pregnancy, and further research is required.…”
Section: Discussionmentioning
confidence: 99%